P230 Once-daily Tiotropium Respimat® Improves Lung Function In Patients With Severe Symptomatic Asthma Independent Of Leukotriene Modifier Use. (10th November 2014) - Dahl, R; Doherty, DE; Corren, J; Karpel, J; Kerstjens, HAM; Engel, M; Moroni-Zentgraf, P; Schmidt, H; Hashimoto, S
Abstract : Background: Once-daily tiotropium Respimat ®, a long-acting anticholinergic bronchodilator, has been shown in a Phase III programme to improve lung function and reduce severe exacerbation risk in patients with severe asthma who remain symptomatic despite using inhaled corticosteroids (ICS) + long-acting β2 -agonist (LABA). Use of pre-trial leukotriene receptor antagonists (LTRAs) was not restricted; we analysed whether pre-screening LTRA use affected tiotropium Respimat ® efficacy. Methods: In two Phase III, replicate, randomised, double-blind, placebo-controlled, parallel-group trials (PrimoTinA-asthma ® : NCT00772538, NCT00776984 ), symptomatic patients received high-dose ICS + LABA and once-daily tiotropium 5 µg or placebo (both delivered via the Respimat ® SoftMist™ inhaler). LTRAs were permitted during run-in and treatment. Co-primary end points were peak and trough forced expiratory volume in 1 second (FEV1 ) responses (difference from baseline) at 24 weeks. Subgroups were defined by pre-screening LTRA use: 'Yes'/'No'. Results: Of 912 randomised patients, 205 reported pre-screening LTRA use, 200 reported LTRA use during the treatment period and 187 had efficacy data at Week 24. Baseline characteristics were comparable between groups. Mean body mass index in LTRA 'Yes'/'No' groups was 27.8 kg/m 2 and 28.3 kg/m 2, respectively. Mean% predicted FEV1 at baseline was 56% in both groups. Lung function responses improved independent of LTRA use: peak FEV1 was 99 ± 50 mL (p = 0.049) in the LTRA 'Yes' group and 113 ± 28 mL (p < 0.001) in the LTRA 'No' group (peak FEV1 improvements independent of concomitant LTRA use [interaction p value=0.6742]). Trough FEV1 (difference from placebo) was 90 ± 46 mL (p = 0.052) in the LTRA 'Yes' group and 93 ± 25 mL (p < 0.001) in the LTRA 'No' group (trough FEV1 improvements independent of concomitant LTRA use [interaction p value = 0.5218]). Conclusion: Once-daily tiotropium Respimat ® added to ICS + LABA improves lung function in patients with severe symptomatic asthma, independent of initial LTRA use.